Finding Love Abroad: Who Marries a Migrant and What Do They Gain? - Eva Dziadula; Madeline Zavodny (Global Labor Organization (GLO), 2023)
This study explores the role of individual and local marriage market characteristics in whether recently wed U.S. residents "imported" a spouse instead of marrying someone already present in the country. Our findings indicate that U.S. natives and immigrants whose spouse is a "marriage migrant" (someone who arrived in the U.S. the same year as the marriage occurred) are positively selected along some dimensions but negatively along others. The results also suggest that U.S. immigration policy plays an important role in whether immigrants bring in a spouse. We further investigate the trade-offs in spouse characteristics associated with having a marriage-migrant spouse. There appear to be several advantages to marrying a migrant, including that marriage-migrant spouses tend to be relatively younger and less likely to have been previously married. Immigrants' gains to marrying a migrant are bigger among naturalized citizens, showcasing the desirability of someone who can easily sponsor a spouse for permanent residence.
Keywords: J12; J15; K37; 330; immigration; marriage markets; assortative matching